Designation of a lectotype for Pseudoceros kylie Newman & Cannon, 1998 (Platyhelminthes, Polycladida, Pseudocerotidae) - Hall, Kathryn A.; Adlard, Robert D. (Zootaxa, 2012)
Recently, we have been examining the literature relevant to Australian “Turbellaria” (Phylum Platyhelminthes) and have noticed that there was an omission in the paper of Newman & Cannon (1998). In this work, Newman & Cannon proposed several new species of Pseudoceros Lang, 1884. There appears to have been an oversight in the typification of one species, Pseudoceros kylie Newman & Cannon, 1998, in that no types were officially designated. Here we recommend new types, which we propose to designate as lectotype and paralectotypes, based on the material examined by Newman & Cannon in their description. All of this material is deposited currently in the Queensland Museum, Australia.